PERAN HUKUM DALAM MENGHADAPI PERUBAHAN SOSIAL DAN KEJAHATAN DUNIA MAYA - Soraya, Bintang Ayu; Permatasari, Dika Arum; Yukamujrisa, Nurlaila (Fakultas Hukum Universitas Sebelas Maret, 2013)
The objective of this research is to get a deep explanation between the role of law in the face of social change and the relation of cybercrime in the society. Itâs included in Act Number 11 of 2008 regarding The Electronic Transaction and information. This research use literary research with normative and judicial approach and the primary law material which is included the secondary data. The analysis technique of this data is using the combination of deductive and inductive. The result of this research show the existence of close relationship between law and social change associated with cyber crime. The Act Number 11 of 2008 regarding The Electronic Transaction and Information is the instrument of social control and social engineering in the society.